2017
DOI: 10.1177/2333794x17696685
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Death in Bangladeshi Children Under 5 Years of Age Hospitalized for Diarrhea and Severe Respiratory Distress in an Urban Critical Care Ward

Abstract: Children with diarrhea hospitalized for respiratory distress often have fatal outcome in resource-limited settings, although data are lacking on risk factors for death in such children. We sought to evaluate clinical predictors for death in such children. In this prospective cohort study, we enrolled under-5 children with diarrhea admitted with severe respiratory distress to the intensive care unit of Dhaka Hospital of International Centre for Diarhoeal Disease Research, Bangladesh, from September 2014 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A high AG metabolic acidosis has also been described in diarrheic children and infants [ 30 , 31 ]. The presence of severe malnutrition, clinical dehydration, sepsis, pneumonia or respiratory distress, drowsiness, meningitis, abdominal distention, and absent peripheral pulses, as well as hypoglycemia, hypoxemia, hypoalbuminemia, hyponatremia and hypernatremia, have been identified as independent predictors of death in diarrheic children [ 28 , 32 35 ]. These results suggest that the prognostic accuracy can be improved in diarrheic children when clinical signs are evaluated in combination with laboratory values, instead of basing prognosis only on the results of laboratory analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A high AG metabolic acidosis has also been described in diarrheic children and infants [ 30 , 31 ]. The presence of severe malnutrition, clinical dehydration, sepsis, pneumonia or respiratory distress, drowsiness, meningitis, abdominal distention, and absent peripheral pulses, as well as hypoglycemia, hypoxemia, hypoalbuminemia, hyponatremia and hypernatremia, have been identified as independent predictors of death in diarrheic children [ 28 , 32 35 ]. These results suggest that the prognostic accuracy can be improved in diarrheic children when clinical signs are evaluated in combination with laboratory values, instead of basing prognosis only on the results of laboratory analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, 15% and 6% of 119,000 total under-5 children deaths are still due to diarrhoea and pneumonia diseases in 2015 [26]. Delay in seeking appropriate care and lack of access to multiple sources for treatment are recognized as the underlying risk factors for children death due to diarrhoea and pneumonia in Bangladesh in several research works [12,13]. Thus, government should focus on the effective interventions of proper life-saving treatment for the children with suspected pneumonia and diarrhoea to achieve the GDDP goals on reducing child mortality due to ARI and diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…No study has also been found conducted at the sub-district or lower administrative units. Most of the studies of ICDDR'B are related to environmental and clinical risk factors of different types of diarrhoeal diseases [12,13]. Using BDHS data, there are studies on modelling diarrhoea or ARI prevalence based on logistic or logistic mixed model for determining their risk factors [14,15], not for prediction purpose since information of the risk factors are not available in the census data.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea, one of the leading causes of death in children younger than five years, accounted for 9% of 5.8 million global deaths and 6% of 0.119 million deaths in Bangladesh in 2015 [34].…”
Section: Ceh In Bangladeshmentioning
confidence: 99%